2016
DOI: 10.3390/insects7040058
|View full text |Cite
|
Sign up to set email alerts
|

Genome Investigations of Vector Competence in Aedes aegypti to Inform Novel Arbovirus Disease Control Approaches

Abstract: Dengue (DENV), yellow fever, chikungunya, and Zika virus transmission to humans by a mosquito host is confounded by both intrinsic and extrinsic variables. Besides virulence factors of the individual arboviruses, likelihood of virus transmission is subject to variability in the genome of the primary mosquito vector, Aedes aegypti. The “vectorial capacity” of A. aegypti varies depending upon its density, biting rate, and survival rate, as well as its intrinsic ability to acquire, host and transmit a given arbov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 130 publications
(145 reference statements)
0
36
0
Order By: Relevance
“…These observations have implications for the further spread of ZIKV into distinct populations of mosquitoes across the globe. There are multiple mechanisms by which the difference in vector capacity among strains could arise, such as genetic variation in metabolic and/or immune pathways, or entry or replication factors necessary for ZIKV infection [ 35 ]. While it is impossible to make any definitive statements on genes that drive differences in vector competency based solely on the location of the microsatellite markers used to analyze genetic variability, we are able to indicate genes that are proximal to the markers driving variability among the groups, particularly AC1 and CT2 ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…These observations have implications for the further spread of ZIKV into distinct populations of mosquitoes across the globe. There are multiple mechanisms by which the difference in vector capacity among strains could arise, such as genetic variation in metabolic and/or immune pathways, or entry or replication factors necessary for ZIKV infection [ 35 ]. While it is impossible to make any definitive statements on genes that drive differences in vector competency based solely on the location of the microsatellite markers used to analyze genetic variability, we are able to indicate genes that are proximal to the markers driving variability among the groups, particularly AC1 and CT2 ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…In Aedes aegpti, targeting male-determining factors using germline Cas9 expression could give similar results 91,96 , though research is at an earlier stage compared with Anopheline systems. Development of constructs which reduce vector competence is another area of active research 89 , with a variety of potential targets having been identified for both malaria 97,98 and arboviruses 99 .…”
Section: Novel Vector Control Technologiesmentioning
confidence: 99%
“…Their feeding behavior not only annoys us, but creates a potent pathway for disease transmission. For example, Aedes aegypti are vectors of viral diseases such as yellow fever, dengue, chikungunya and Zika [1, 2]. Certain mosquito species like Ae.…”
Section: Introductionmentioning
confidence: 99%